Relative importance of social factors linked to academic achievement in the 1st grade - Šarūnė Magelinskaitė-Legkauskienė; Visvaldas Legkauskas; Albina Kepalaitė (Social Welfare: Interdisciplinary Approach)
The present study was aimed at investigating aspects of social functioning linked to academic achievement in the 1st grade. Subjects were 380 Lithuanian 1st graders, 211 girls and 169 boys. Social factors measured included student social competence, student-teacher relationship, and popularity in class. Regression analysis revealed that learning-related social competence – ability to take directions - was a strongest predictor, accounting for 28.7% of variance in academic achievement